New approach to develop ultra-high inhibitory drug using the power function of the stoichiometry of the targeted nanomachine or biocomplex - Shu, Dan (Nanomedicine (Lond), 2015)
AIMS: To find methods for potent drug development by targeting to biocomplex with high copy number. METHODS: Phi29 DNA packaging motor components with different stoichiometries were used as model to assay virion assembly with Yang Hui's Triangle [Image: see text] , where Z = stoichiometry, M = drugged subunits per biocomplex, p and q are the fraction of drugged and undrugged subunits in the population. RESULTS: Inhibition efficiency follows a power function. When number of drugged subunits to block the function of the complex K = 1, the uninhibited biocomplex equals q(z), demonstrating the multiplicative effect of stoichiometry on inhibition with stoichiometry 1000 > 6 > 1. Complete inhibition of virus replication was found when Z = 6. CONCLUSION: Drug inhibition potency depends on the stoichiometry of the targeted components of the biocomplex or nanomachine. The inhibition effect follows a power function of the stoichiometry of the target biocomplex.